Estabelecimento de plantas nativas da caatinga em um gradiente de salinidade do solo, sob condições controladas - Bessa, Michele Campos (2012)
Salinity is one of the abiotic stresses that most limits crop production because of its negative effects on plant growth and development. In areas degraded by salts it appears that the establishment of tree species is not easy, especially in rainfed crops and regions with very low precipitation. The objective of this study is to evaluate the establishment of twelve species of woody plants native to the Caatinga in a gradient of soil salinity in greenhouse, in order to obtain grants for the establishment of promising species under field conditions. The work was divided into two steps: 1. Growth and degree of salinity tolerance of twelve native species of Caatinga in a protected environment - The experimental design was randomized blocks in split plots with seedlings in the plot of twelve native species of the Caatinga (Aroeira, Ipê roxo, Mororó, Mulungu, Sabiá, Pau-mocó, Angico, Catanduva, Frei Jorge, Jurema branca, Tamboril, e Jurema preta) and subplots, the five levels of soil salinity (1.2, 2.7, 4.7, 6.7, 8,4 dS m-1), with five replicates. For moderate levels of soil salinity was found that all species are as tolerant or moderately tolerant to salinity. Considering the degree of reduction in total dry matter production, the highest level of salinity, it was observed that only the mastic proved to be tolerant to salinity (T); The Ipê and mulungu behaved as moderately tolerant (MT); the mororó and pau-mocó moderately susceptible (MS); most species, sabiá, angico, catanduva, frei jorge, jurema branca, jurema preta and tamboril, were classified as sensitive (S), with reductions of more than 60%. 2. Gas exchange and concentration of organic and inorganic solutes in six species native to the Caatinga under saline conditions - The design was randomized blocks in split plots with the plot six native species of Caatinga (Aroeira, Ipê roxo, Mororó, Mulungu, Sabiá e Pau-mocó,), which showed different degrees of salinity tolerance (step 1), and subplot five levels of soil salinity (1.2, 2.7, 4.7, 6.7, 8.4 dS m-1), with five replicates. Salinity caused reduction in leaf gas exchange, and this effect is independent of the species studied. However, observe a greater stomatal control and greater intrinsic efficiency of water use in species with higher degrees of salt tolerance, ie, aroeira, ipê roxo and mulungu. In the present study could not establish a clear relationship between the accumulation of organic solutes studied and salt tolerance of six species native to the Caatinga. However, observed a strong correlation between the Na/K and Na in the leaves and the degree of tolerance of species with species more tolerant of minor variations and presenting lower values ​​with increasing soil salinity.